Human emotional odours influence horses’ behaviour and physiology - Plotine Jardat; Alexandra Destrez; Fabrice Damon; Noa Tanguy-Guillo; Anne-Lyse Lainé; Céline Parias; Fabrice Reigner; Vitor H. B. Ferreira; Ludovic Calandreau; Léa Lansade (PLoS ONE, 2026)
Olfaction is the most widespread sensory modality animals use to communicate, yet much remains to be discovered about its role. While most studies focused on intraspecific interactions and reproduction, new evidence suggests chemosignals may influence interspecific interactions and emotional communication. This study explores this possibility, investigating the potential role of olfactory signals in human-horse interactions. Cotton pads carrying human odours from fear and joy contexts, or unused pads (control odour) were applied to 43 horses’ nostrils during fear tests (suddenness and novelty tests) and human interaction tests (grooming and approach tests). Principal component analysis showed that overall, when exposed to fear-related human odours, horses exhibited significantly heightened fear responses and reduced interaction with humans compared to joy-related and control odours. More precisely, when exposed to fear-related odours, horses touched the human less in the human approach test (effect size: Rate Ratio(RR)=0.60 ± 0.24), gazed more at the novel object (RR = 1.32 ± 0.14), and were more startled (startle intensity – Cohen’s d = −0.88 ± 0.39; and maximum heart rate – Cohen’s d = 1.16 ± 0.47) by a sudden event. These results highlight the significance of chemosignals in interspecific interactions and provide insights into questions about the impact of domestication on emotional communication. Moreover, these findings have practical implications regarding the significance of handlers’ emotional states and its transmission through odours during human-horse interactions.